Epileptogenic Zone Localization With 18FDG PET Using a New Dynamic Parametric Analysis - Mayoral, Maria; Niñerola-Baizán, Aida; Marti-Fuster, Berta; Donaire, Antonio; Perissinotti, Andrés; Rumià, Jordi; Bargalló, Núria; Sala-Llonch, Roser; Pavia, Javier; Ros, Domènec; Carreño, Mar; Pons, Francesca; et al. (Frontiers in Neurology, 2019)
Introduction: [18F]fluorodeoxyglucose (18F-FDG) positron emission tomography (PET) is part of the regular preoperative work-up in medically refractory epilepsy. As a complement to visual evaluation of PET, statistical parametric maps can help in the detection of the epileptogenic zone (EZ). However, software packages currently available are time-consuming and little intuitive for physicians. We develop a user-friendly software (referred as PET-analysis) for EZ localization in PET studies that allows dynamic real-time statistical parametric analysis. To evaluate its performance, the outcome of PET-analysis was compared with the results obtained by visual assessment and Statistical Parametric Mapping (SPM). Methods: Thirty patients with medically refractory epilepsy who underwent presurgical 18F-FDG PET with good postoperative outcomes were included. The 18F-FDG PET studies were evaluated by visual assessment, with SPM8 and PET-analysis. In SPM, parametric T-maps were thresholded at corrected p<0.05 and cluster size k=50 and at uncorrected p<0.001 and k=100 (the most used parameters in the literature). Since PET-analysis rapidly processes different threshold combinations, T-maps were thresholded with multiple p-value and different clusters sizes. The presurgical EZ identified by visual assessment, SPM and PET-analysis was compared to the confirmed EZ according to postsurgical follow-up. Results: PET-analysis obtained 66.7% (20/30) of correctly localizing studies, comparable to the 70.0% (21/30) achieved by visual assessment and significantly higher (p<0.05) than that obtained with the SPM threshold p<0.001/k=100, of 36.7% (11/30). Only one study was positive, albeit non-localizing, with the SPM threshold corrected p<0.05/k=50. Concordance was substantial for PET-analysis (к=0.643) and visual interpretation (к=0.622), being fair for SPM (к=0.242). Conclusion: Compared to SPM with the fixed standard parameters, PET-analysis may be superior in EZ localization with its easy and rapid processing of different threshold combinations. The results of this initial proof-of-concept study validate the clinical use of PET-analysis as a robust objective complementary tool to visual assessment for EZ localization.